Foamed particles, bead foamed molded article, base resin composition for foaming, and base resin composition pellets
By using a base resin composition containing a polyarylether-based resin, a polystyrene-based resin and a metal salt, the foaming process is optimized, and the problem of insufficient foaming and molding in the prior art is solved, and a foamed molded body with high heat resistance and mechanical strength is realized.
Patent Information
- Application Number
- CN202411365897.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-06
- Filing Date
- 2024-09-29
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the foamability and moldability are insufficient, resulting in insufficient heat resistance and mechanical strength of the foamed molded body, and it is difficult to meet the requirements of high heat resistance and mechanical characteristics at the same time.
The base resin composition containing a polyarylether-based resin, a polystyrene-based resin and a metal salt is used to optimize the foaming process to improve moldability and heat resistance by controlling the content and particle size of the metal salt.
The foamed particles with good moldability and the bead foamed molded body with excellent heat resistance are realized, which can meet the needs of high mechanical strength and good appearance at the same time.
Smart Images

Figure BDA0005066203530000061 
Figure BDA0005066203530000321 
Figure BDA0005066203530000331
Abstract
Description
Technical Field
[0001] The present invention relates to foamed particles, bead foamed molded products, a base resin composition for foaming, and base resin composition pellets. Background Art
[0002] In automobile peripheral parts and electronic equipment peripheral parts, with the recent high output, large capacity, and large size, the demand for resin foams that are not prone to dimensional changes even after long-term high-temperature heat treatment is increasing (hereinafter in this specification, small dimensional changes after long-term high-temperature heat treatment are sometimes expressed as high heat resistance). In addition, with the thin-walled and complex-shaped parts, the requirements for processability such as dimensional accuracy and thin-wall moldability for resin foams are also increasing. In addition, the demand for high-strength resin foams while maintaining the lightweight of parts is also increasing.
[0003] As a resin foam having high heat resistance and strength, polyarylether / polystyrene resin foams are widely used. For example, polyphenylene ether / polystyrene resin foams are disclosed in Patent Document 1. However, in the resin foam described in Patent Document 1, although the proportion of polyarylether having high heat resistance is high relative to the overall resin composition, the glass transition temperature is reduced due to the mixing of a liquid flame retardant, resulting in insufficient heat resistance.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2011-019057 Summary of the invention
[0007] Problems to be solved by the invention
[0008] Regarding Patent Document 1, in order to further improve the heat resistance, a method of increasing the proportion of the polyarylether resin in the resin composition is considered. However, in this method, the amount of inorganic gas impregnated into the resin composition is reduced, so the foaming property is significantly reduced, which has the problem of being difficult to obtain foamed particles with excellent moldability and difficult to obtain a foamed body with excellent heat resistance and mechanical strength.
[0009] In addition, since the glass transition temperature of the resin composition is increased, the amount of heat required for foaming is increased, which easily causes insufficient heating or uneven heating, and it is difficult to obtain foamed particles with excellent moldability and a foamed body with excellent heat resistance and mechanical strength.
[0010] On the other hand, there is a method of using hydrocarbon gas as a gas that is easier to impregnate into the resin, but the gas remains in the foamed particles after foaming, and plasticization occurs due to the residual gas, making it difficult to obtain a foamed product with excellent heat resistance and mechanical strength.
[0011] That is, in the prior art, foamability and formability are insufficient, and the heat resistance and mechanical strength of the obtained foamed molded product are insufficient. In order to be suitable for the above-mentioned purposes, it is hoped that further improvement will be made. A trade-off relationship is formed between high heat resistance, mechanical properties and foamability and formability, and it is difficult to satisfy both at the same time, and a new technology for solving this problem is needed.
[0012] Therefore, the object of the present invention is to provide foamed particles with good formability and bead foamed molded products with excellent heat resistance. In addition, the object of the present invention is to provide a foaming base resin composition and base resin composition pellets that can obtain foamed particles with good formability and foamed molded products with excellent heat resistance.
[0013] Means for solving problems
[0014] The present invention is as follows. [1]
[0016] A foamed particle is formed by foaming a base resin composition, wherein:
[0017] The above-mentioned substrate resin composition comprises:
[0018] (a) polyarylether resin,
[0019] (b) polystyrene resin, and
[0020] (c) a metal salt,
[0021] 0.01 to 1 parts by mass of (c) a metal salt is contained with respect to 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin,
[0022] The (c) metal salt is an oxide and / or sulfide of at least one metal selected from the group consisting of aluminum, magnesium, tin, zinc, titanium, chromium, manganese, nickel, cobalt and iron. [2]
[0024] The expanded beads as described in [1], wherein the average particle size of the metal salt (c) is 0.5 μm or less. [3]
[0026] The expanded beads according to [1] or [2], wherein the metal salt (c) is an oxide and / or sulfide of zinc and / or titanium. [4]
[0028] The expanded beads as described in [3], wherein the (c) metal salt is a sulfide of zinc and / or titanium. [5]
[0030] The foamed beads as described in [3], wherein the metal salt (c) is zinc oxide and / or zinc sulfide. [6]
[0032] The foamed particles as described in [3], wherein the (c) metal salt is zinc sulfide. [7]
[0034] The foamed beads according to any one of [1] to [6], wherein the base resin composition contains 0 to 0.1 parts by mass of (d) a flame retardant based on 100 parts by mass of the total mass of (a) the polyarylether resin and (b) the polystyrene resin. [8]
[0036] The expanded beads according to any one of [1] to [7], wherein the base resin composition has a glass transition temperature of 145 to 200°C. [9]
[0038] The expanded beads according to any one of [1] to [8], wherein the mass ratio (a) / (b) of the (a) polyarylether-based resin to the (b) polystyrene-based resin is 1.50 or more.
[10]
[0040] The foamed beads according to any one of [1] to [9], wherein the base resin composition contains 0 to 0.05 parts by mass of (e) a phosphorus-based antioxidant based on 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin.
[11]
[0042] The foamed beads according to any one of [1] to
[10] , wherein the base resin composition contains 0 to 0.05 parts by mass of (f) a hindered phenol antioxidant based on 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin.
[12]
[0044] The foamed beads according to any one of [1] to
[11] , wherein the base resin composition contains 0 to 0.05 parts by mass of (g) a hindered amine light stabilizer based on 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin.
[13]
[0046] A beads foam molded product comprising the foamed beads according to any one of [1] to
[12] .
[14]
[0048] The beads foam molded product as described in
[13] , wherein the closed cell ratio of the beads foam molded product is 90% or more.
[15]
[0050] A foaming substrate resin composition, comprising:
[0051] (a) polyarylether resin,
[0052] (b) polystyrene resin, and
[0053] (c) a metal salt,
[0054] It is characterized in that
[0055] 0.01 to 1 parts by mass of (c) a metal salt is contained with respect to 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin,
[0056] The (c) metal salt is an oxide and / or sulfide of at least one metal selected from the group consisting of aluminum, magnesium, tin, zinc, titanium, chromium, manganese, nickel, cobalt and iron.
[16]
[0058] A substrate resin composition pellet comprising:
[0059] (a) polyarylether resin,
[0060] (b) polystyrene resin, and
[0061] (c) a metal salt,
[0062] It is characterized in that
[0063] 0.01 to 1 parts by mass of (c) a metal salt is contained with respect to 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin,
[0064] The metal salt (c) is an oxide and / or sulfide of at least one metal selected from the group consisting of aluminum, magnesium, tin, zinc, titanium, chromium, manganese, nickel, cobalt and iron,
[0065] The sphericity of the above-mentioned base resin composition pellets is 1.00 to 1.20,
[0066] The average particle size of the base resin composition pellets is 0.50 mm to 1.10 mm.
[0067] Effects of the Invention
[0068] According to the present invention, it is possible to provide foamed particles with good formability and bead foaming molded products with excellent heat resistance. In addition, according to the present invention, it is possible to provide a foaming substrate resin composition and a substrate resin composition pellet that can obtain foamed particles with good formability and foaming molded products with excellent heat resistance. DETAILED DESCRIPTION
[0069] The specific embodiment of the present invention (hereinafter also referred to as "this embodiment") is described in detail below. It should be noted that the present invention is not limited to the following embodiment, and can be implemented with various modifications within the scope of the gist thereof.
[0070] [Base resin composition]
[0071] The base resin composition of the present embodiment is a foaming base resin composition for obtaining a foamed molded article. The base resin composition of the present embodiment can be foamed to produce foamed particles for obtaining a bead foamed molded article, or a foamed molded article can be directly produced.
[0072] The base resin composition of the present embodiment contains (a) a polyarylether-based resin, (b) a polystyrene-based resin, and (c) a metal salt.
[0073] <(a) Polyarylene Ether Resin>
[0074] The (a) polyarylether-based resin is not particularly limited as long as it has an arylene group and an ether bond in its main skeleton. Examples of the arylene group include linking groups including a phenylene group, a biphenyl group, a naphthyl group, and the like.
[0075] In the present embodiment, (a) the polyarylether-based resin is preferably a polyphenylene ether-based resin, and examples thereof include polyphenylene ether resin, polyphenylene ether resin / polystyrene resin alloy, polyphenylene ether resin / high-impact polystyrene resin alloy, or polyphenylene ether resin / polystyrene resin / high-impact polystyrene resin alloy.
[0076] These may be used alone or in combination of two or more.
[0077] The details of the polyphenylene ether-based resin are described below.
[0078] The polyphenylene ether resin of the polyphenylene ether-based resin refers to a polymer containing a repeating unit (structural unit) represented by the following general formula (I), and examples thereof include a homopolymer composed of a repeating unit represented by the following general formula (I), and a copolymer containing a repeating unit represented by the following general formula (I).
[0079] [Chemistry 1]
[0080]
[0081] In the general formula (I), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, a phenyl group, or a halogenated alkyl group or a halogenated alkoxy group having at least 2 carbon atoms between the halogen atom and the benzene ring in the general formula (I) and not containing an α-tertiary carbon atom. In the general formula (I), n is an integer representing the degree of polymerization.
[0082] Specific examples of the polyphenylene ether resin include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2-methyl-6-propyl-1,4-phenylene) ether, poly(2,6-dipropyl-1,4-phenylene) ether, poly(2-ethyl-6-propyl-1,4-phenylene) ether, poly(2,6-dibutyl-1,4-phenylene) ether, poly(2,6-dilauryl-1,4-phenylene) ether, poly(2,6-diphenyl-1,4-diphenylene) ether, poly(2,6 -dimethoxy-1,4-phenylene) ether, poly(2,6-diethoxy-1,4-phenylene) ether, poly(2-methoxy-6-ethoxy-1,4-phenylene) ether, poly(2-ethyl-6-stearoyloxy-1,4-phenylene) ether, poly(2,6-dichloro-1,4-phenylene) ether, poly(2-methyl-6-phenyl-1,4-phenylene) ether, poly(2,6-dibenzyl-1,4-phenylene) ether, poly(2-ethoxy-1,4-phenylene) ether, poly(2-chloro-1,4-phenylene) ether, poly(2,6-dibromo-1,4-phenylene) ether, etc., but are not limited to these. Among them, R in the general formula (I) is particularly preferred 1 and R 2 is an alkyl group having 1 to 4 carbon atoms, R 3 and R 4 A substance which is hydrogen or an alkyl group having 1 to 4 carbon atoms.
[0083] The method for producing the polyphenylene ether resin is not particularly limited and can be produced by a known method, for example, a complex of a cuprous salt and an amine based on Hay described in the specification of U.S. Pat. No. 3,306,874 can be used as a catalyst, and 2,6-xylenol can be easily produced by oxidative polymerization. In addition, the method described in the specification of U.S. Pat. No. 3,306,875, the specification of U.S. Pat. No. 3,257,357, the specification of U.S. Pat. No. 3,257,358, the publication of Japanese Patent Publication No. 52-17880, the publication of Japanese Patent Publication No. 50-51197, and the publication of Japanese Patent Publication No. 63-152628 can also be cited.
[0084] In the present embodiment, as the polyphenylene ether-based resin, a modified polyphenylene ether resin in which a part or all of the structural units constituting the polyphenylene ether resin are modified with an unsaturated or saturated carboxylic acid or a derivative thereof can be used.
[0085] Examples of the modified polyphenylene ether resin include those described in Japanese Patent Application Laid-Open No. 2-276823 (U.S. Patent No. 5,159,027, U.S. Reissued Patent No. 35,695), Japanese Patent Application Laid-Open No. 63-108059 (U.S. Patent Nos. 5,214,109 and 5,216,089), and Japanese Patent Application Laid-Open No. 59-59724.
[0086] The modified polyphenylene ether resin can be produced, for example, by melt-kneading an unsaturated or saturated carboxylic acid or a derivative thereof in a polyphenylene ether resin in the presence or absence of a free radical initiator to carry out a reaction, thereby producing the modified polyphenylene ether resin. Alternatively, the modified polyphenylene ether resin and an unsaturated or saturated carboxylic acid or a derivative thereof are dissolved in an organic solvent in the presence or absence of a free radical initiator, and reacted in a solution, thereby producing the modified polyphenylene ether resin.
[0087] Examples of unsaturated carboxylic acids or their derivatives include maleic acid, fumaric acid, itaconic acid, halogenated maleic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, and bridged-cis-bicyclo(2,2,1)-5-heptene-2,3-dicarboxylic acid; anhydrides, esters, amides, imides, etc. of these dicarboxylic acids; and acrylic acid, methacrylic acid, etc.; esters, amides, etc. of these monocarboxylic acids.
[0088] Examples of saturated carboxylic acids or derivatives thereof include compounds that are thermally decomposed at the reaction temperature during production of the modified polyphenylene ether resin to form derivatives of the modified polyphenylene ether resin, such as malic acid and citric acid.
[0089] The polyphenylene ether resin may be a resin consisting of only polyphenylene ether resin, wherein the polyphenylene ether resin is 100% by mass, or may be the polymer alloy. In the case of the polymer alloy, from the perspective of heat resistance and flame retardancy, the content of the polyphenylene ether resin in 100% by mass of the polymer alloy is preferably 30 to 99% by mass, more preferably 40 to 80% by mass, and further preferably 50 to 70% by mass.
[0090] The weight average molecular weight (Mw) of the (a) polyarylether resin is preferably 20,000 to 90,000, more preferably 40,000 to 80,000, and further preferably 50,000 to 75,000. If the weight average molecular weight of the (a) polyarylether resin is 20,000 or more, the resin bubble rupture during foaming can be fully suppressed. In addition, if the weight average molecular weight of the (a) polyarylether resin is 90,000 or less, the melt viscosity of the resin will not become too high, and there is a tendency that the granulation step (manufacturing of substrate resin composition pellets) in the manufacture of the foamed particles described later can be well granulated without the die pressure reaching the processing upper limit.
[0091] The weight average molecular weight (Mw) can be determined by measuring the resin by gel permeation chromatography (GPC) and using a calibration curve obtained by measuring commercially available standard polystyrene (created using the peak molecular weight of standard polystyrene) to determine the peak molecular weight of the chromatogram.
[0092] The content of the (a) polyarylene ether-based resin is preferably 30 to 99% by mass, more preferably 40 to 80% by mass, and even more preferably 50 to 70% by mass, based on 100% by mass of the base resin composition.
[0093] <(b) Polystyrene Resin>
[0094] (b) The polystyrene resin refers to a homopolymer of styrene and a styrene derivative, and a copolymer containing styrene and a styrene derivative as a main component (containing 50% by mass or more of the components in the polystyrene resin).
[0095] Examples of the styrene derivatives include o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, α-methylstyrene, β-methylstyrene, diphenylethylene, chlorostyrene, and bromostyrene.
[0096] Examples of the (b) polystyrene-based resin which is a homopolymer include polystyrene, poly-α-methylstyrene, and polychlorostyrene.
[0097] Examples of the (b) polystyrene resins that are copolymers include: binary copolymers such as styrene-butadiene copolymers, styrene-acrylonitrile copolymers, styrene-maleic acid copolymers, styrene-maleic anhydride copolymers, styrene-maleimide copolymers, styrene-N-phenylmaleimide copolymers, styrene-N-alkylmaleimide copolymers, styrene-N-alkyl-substituted phenylmaleimide copolymers, styrene-acrylic acid copolymers, styrene-methacrylic acid copolymers, styrene-methyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-n-alkyl acrylate copolymers, styrene-n-alkyl methacrylate copolymers, and ethylvinylbenzene-divinylbenzene copolymers; terpolymers such as ABS and butadiene-acrylonitrile-α-methylbenzene copolymers; graft copolymers such as styrene-grafted polyethylene, styrene-grafted ethylene-vinyl acetate copolymers, (styrene-acrylic acid) grafted polyethylene, and styrene-grafted polyamide; and the like.
[0098] These may be used alone or in combination of two or more.
[0099] The content of the (b) polystyrene-based resin is preferably 1 to 70% by mass, more preferably 20 to 60% by mass, and even more preferably 30 to 50% by mass, based on 100% by mass of the base resin composition.
[0100] In the present embodiment, the mass ratio (a) / (b) of the (a) polyarylether resin to the (b) polystyrene resin is preferably 0.50 or more, more preferably 1.00 or more, further preferably 1.30 or more, further preferably 1.50 or more, and most preferably 2.00 or more. If the mass ratio (a) / (b) of the (a) polyarylether resin to the (b) polystyrene resin is 0.50 or more, there is a tendency to show higher heat resistance. The upper limit of the mass ratio (a) / (b) of the (a) polyarylether resin to the (b) polystyrene resin is not particularly limited, and for example, it can be 5.00 or less.
[0101] The polystyrene-based resin can be produced by any conventionally known production method.
[0102] <(c) Metal Salt>
[0103] (c) The metal salt is an oxide and / or sulfide of at least one metal selected from the group consisting of aluminum, magnesium, tin, zinc, titanium, chromium, manganese, nickel, cobalt and iron.
[0104] Specifically, aluminum oxide, magnesium oxide, tin oxide (SnO, SnO2, etc.), zinc oxide, titanium oxide (TiO, TiO2, etc.), chromium oxide, manganese oxide (MnO, Mn3O4, Mn2O3, MnO2, Mn2O7, etc.), nickel oxide (NiO, etc.), cobalt oxide (CoO, etc.), iron oxide (FeO, Fe2O3, Fe3O4, etc.), aluminum sulfide, magnesium sulfide, tin sulfide (SnS, etc.), zinc sulfide, titanium sulfide, chromium sulfide, manganese sulfide, nickel sulfide, cobalt sulfide, iron sulfide (FeS, etc.), etc. (c) The metal salt is preferably an oxide and / or sulfide of zinc and / or titanium (i.e., at least one selected from the group consisting of zinc oxide, titanium oxide, zinc sulfide and titanium sulfide). From the perspective of heat resistance, the metal salt (c) is more preferably a sulfide of zinc and / or titanium (i.e., zinc sulfide and / or titanium sulfide), and is further preferably zinc sulfide (ZnS). From the perspective of compressive strength, the metal salt (c) is preferably zinc oxide or zinc sulfide.
[0105] These (c) metal salts may be used alone or in combination of two or more.
[0106] In this embodiment, (c) metal salt has the following effect: using a very small amount of compounding, bubble nuclei can be generated in the base resin composition at the same time and multiple times during foaming. There are known examples of substances that promote the generation of bubble nuclei, all of which have a tendency to impair heat resistance and mechanical properties relative to the compounding amount required for the base resin composition.
[0107] In the present embodiment, (c) metal salt can be a small amount of compounding amount, as a result, can further reduce the average bubble diameter of expanded particles, minimize the deviation of bubble diameter when foamability, formability, heat resistance, mechanical properties are not damaged. As described below, the more the average bubble diameter is small, the smaller the deviation of bubble diameter is, the higher the independent bubble rate of expanded particles is, and formability, foamability are more excellent. As a result, it is possible to obtain the thin-walled bead foaming molding that was difficult to mold in the past, the heat resistance, mechanical properties, and excellent appearance.
[0108] The content of the metal salt (c) is 0.01 to 1 part by mass, preferably 0.05 to 0.5 part by mass, and more preferably 0.1 to 0.3 part by mass relative to 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin, from the viewpoint of reducing the average cell diameter and lowering the variation in the cell diameter even in a composition having a high glass transition temperature Tg and a large amount of heat required for foaming.
[0109] When the content of the (c) metal salt is 0.01 parts by mass or more relative to 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin, it is possible to suppress the extreme reduction of the bubble nuclei, suppress the coarsening of the bubble diameters, and suppress the increase in the deviation of the bubble diameters, thereby obtaining foamed particles with good foamability and moldability, and foamed molded products with excellent heat resistance, mechanical properties and appearance.
[0110] When the content of the (c) metal salt is 1 part by mass or less relative to 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin, the aggregation of the (c) metal salts can be suppressed, and the effect of reducing the bubble diameter can be fully exerted, so that foamed particles with good foamability and moldability, and foamed molded products with excellent heat resistance, mechanical properties and appearance can be obtained.
[0111] The average particle size of the metal salt (c) is preferably 0.5 μm or less, more preferably 0.4 μm or less, and further preferably 0.3 μm or less. The lower limit of the average particle size of the metal salt (c) is not particularly limited, and may be, for example, 0.1 μm or more. If the average particle size of the metal salt (c) is 0.5 μm or less, the effect of reducing the bubble diameter increases, and the heat resistance, mechanical properties and appearance of the foamed molded article tend to be improved.
[0112] <Additives>
[0113] The base resin composition of the present embodiment may further contain additives such as (d) a flame retardant, (e) a phosphorus-based antioxidant, (f) a hindered phenol-based antioxidant, (g) a hindered amine-based light stabilizer, and (h) other additives.
[0114] (d) Flame retardant
[0115] The base resin composition of the present embodiment may contain (d) a flame retardant.
[0116] From the perspective of exhibiting high heat resistance, the content of the (d) flame retardant is preferably 0 to 20 parts by mass, more preferably 0 to 5 parts by mass, further preferably 0 to 0.1 parts by mass, relative to 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin in the base resin composition, and most preferably substantially no (d) flame retardant is contained (below the detection limit in analysis using NMR, ICP emission spectroscopy, etc.).
[0117] The flame retardant (d) is not particularly limited, and examples thereof include organic flame retardants and inorganic flame retardants.
[0118] Examples of the organic flame retardant include halogen compounds represented by bromine compounds, and non-halogen compounds represented by phosphorus compounds and silicone compounds.
[0119] Examples of the inorganic flame retardant include metal hydroxides represented by aluminum hydroxide and magnesium hydroxide, and antimony compounds represented by antimony trioxide and antimony pentoxide.
[0120] These may be used alone or in combination of two or more.
[0121] Among the flame retardants mentioned above, non-halogen flame retardants of organic flame retardants are preferred from the viewpoint of environmental friendliness, and phosphorus flame retardants and silicone flame retardants are more preferred.
[0122] Among the phosphorus-based flame retardants, substances containing phosphorus or phosphorus compounds can be used. As phosphorus, red phosphorus can be mentioned. In addition, as phosphorus compounds, phosphate esters, phosphazene compounds having a bond between a phosphorus atom and a nitrogen atom in the main chain, trialkylphosphine oxides, triphenylphosphine oxides, etc. can be mentioned.
[0123] Examples of the phosphoric acid ester include trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixyl phosphate, tolylene diphenyl phosphate, xylyl phenyl phosphate, dimethyl ethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, hydroxyphenyl diphenyl phosphate, and resorcinol bis(diphenyl phosphate). Examples include phosphoric acid ester compounds of the type in which these are modified with various substituents, various condensed phosphoric acid ester compounds, and phosphoric acid ester compounds having a cyclic structure.
[0124] Among them, phosphazene compounds, triphenyl phosphate, condensed phosphate compounds, and phosphate compounds having a cyclic structure are preferred from the viewpoint of heat resistance, flame retardancy, and foaming properties.
[0125] These may be used alone or in combination of two or more.
[0126] In addition, examples of silicone-based flame retardants include (mono- or poly-)organosiloxanes.
[0127] Examples of the (mono- or poly-)organosiloxane include monoorganosiloxanes such as dimethylsiloxane and phenylmethylsiloxane; polydimethylsiloxane and polyphenylmethylsiloxane obtained by polymerizing these; and organopolysiloxanes such as copolymers thereof.
[0128] In the case of organopolysiloxane, the bonding groups of the main chain and the branched side chains are hydrogen, alkyl, phenyl, preferably phenyl, methyl, ethyl, propyl, but not limited thereto. The terminal bonding groups may be hydroxyl, alkoxy, alkyl, phenyl. The shape of silicones is also not particularly limited, and any shape such as oily, rubbery, varnish-like, powdery, and granular can be used.
[0129] These may be used alone or in combination of two or more.
[0130] The melting point of the flame retardant is not particularly limited, but is preferably 30° C. or higher, more preferably 50° C. or higher, and further preferably 100° C. or higher (or has no melting point).
[0131] The decomposition temperature of the flame retardant is not particularly limited, but is preferably 200° C. or higher, more preferably 250° C. or higher, and further preferably 280° C. or higher. The decomposition temperature is preferably within the above range from the viewpoint of improving production stability in the production process of the base resin composition.
[0132] The decomposition temperature can be defined as a 5 wt% weight loss temperature, and can be measured, for example, by measuring weight loss using a differential thermal-thermogravimetric simultaneous measurement apparatus (TG-DTA).
[0133] (e) Phosphorus antioxidants
[0134] (e) Phosphorus-based antioxidants are not particularly limited as long as they are antioxidants containing phosphorus, and examples thereof include ADKSTAB PEP series (manufactured by ADEKA) and Irgafos series (manufactured by BASF).
[0135] The content of the (e) phosphorus-based antioxidant is preferably 0 to 0.1 parts by mass, more preferably 0 to 0.05 parts by mass, further preferably 0 to 0.01 parts by mass, and most preferably substantially free of the (e) phosphorus-based antioxidant (less than the detection limit in analysis by NMR, ICP emission spectroscopy, FT-IR, etc.) relative to 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin. When the content of the (e) phosphorus-based antioxidant is 0.1 parts by mass or less relative to 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin, the effect of the (c) metal salt in generating bubble nuclei tends to be well exerted.
[0136] (f) Hindered phenol antioxidants
[0137] (f) Hindered phenol antioxidants are not particularly limited as long as they are antioxidants having a hindered phenol structure, and examples thereof include ADKSTAB AO series (manufactured by ADEKA) and Irganox series (manufactured by BASF).
[0138] The content of the (f) hindered phenol antioxidant is preferably 0 to 0.1 parts by mass, more preferably 0 to 0.05 parts by mass, further preferably 0 to 0.01 parts by mass, and most preferably substantially no (less than the detection limit in analysis by NMR, FT-IR, etc.) hindered phenol antioxidant is mixed with 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin. When the content of the (f) hindered phenol antioxidant is 0.1 parts by mass or less, the effect of the (c) metal salt in generating bubble nuclei tends to be well exerted, relative to 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin.
[0139] (g) Hindered amine light stabilizer
[0140] (g) Hindered amine light stabilizer is not particularly limited as long as it is an antioxidant having a hindered amine structure, and examples thereof include ADKSTAB LA series (manufactured by ADEKA) and Tinuvin series (manufactured by BASF).
[0141] The content of the (g) hindered amine light stabilizer is preferably 0 to 0.1 parts by mass, more preferably 0 to 0.05 parts by mass, further preferably 0 to 0.01 parts by mass, and most preferably substantially no (less than the detection limit in analysis by NMR, FT-IR, etc.) hindered amine light stabilizer is mixed with 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin. When the content of the (g) hindered amine light stabilizer is 0.1 parts by mass or less, the effect of the (c) metal salt on the generation of bubble nuclei tends to be well exerted.
[0142] (h) Other additives
[0143] Examples of (h) other additives other than the above include flame retardants, heat stabilizers, antioxidants other than the above components (e) to (f), antistatic agents, inorganic fillers, anti-dripping agents, ultraviolet absorbers, light absorbers, plasticizers, mold release agents, dyes-pigments, rubber components, resins other than the above-mentioned base resins (components (a) and (b)), etc., and they can be added within a range that does not impair the effects of the present invention.
[0144] As the content of (h) other additives, with the mass of the base resin (the total mass of (a) polyarylether resin and (b) polystyrene resin) being 100 parts by mass, the content of (h) other additives is preferably 0 to 40 parts by mass, more preferably 0 to 20 parts by mass, and even more preferably 0 to 5 parts by mass.
[0145] <Glass transition temperature Tg of base resin composition>
[0146] In the present embodiment, from the aspect of showing excellent heat resistance, the glass transition temperature Tg of the substrate resin composition is preferably 130°C or more, more preferably 145°C or more, further preferably 155°C or more, and most preferably 170°C or more. If the glass transition temperature Tg is 130°C or more, there is a tendency for better heat resistance. In addition, the glass transition temperature Tg of the substrate resin composition is preferably 220°C or less, more preferably 200°C or less, and further preferably 190°C or less. If the glass transition temperature is 220°C or less, the temperature at which the foaming molded body can be molded will not be too high during the foaming of the foaming molded body, and there is a tendency for the foaming molded body to be easily molded.
[0147] The glass transition temperature Tg of the base resin composition can be adjusted by mixing resins with different glass transition temperatures Tg. For example, if the mixing ratio of the resin with a high glass transition temperature Tg is increased, the glass transition temperature Tg of the base resin composition increases. In addition, if the mixing ratio of the flame retardant (d) compatible with the base resin composition is increased, the glass transition temperature Tg of the base resin composition decreases.
[0148] The glass transition temperature Tg of the base resin composition is the peak temperature of the loss tangent (tan δ) peak obtained by dynamic viscoelasticity measurement, and can be measured by the method described in Examples below.
[0149] [Method for producing base resin composition]
[0150] The method for producing the base resin composition is not particularly limited, and examples thereof include a method of mixing the mixture using a Henschel mixer, a tumble mixer, a V-type mixer, etc., and then kneading the mixture using a single-screw or multi-screw extruder, a heating roll, a kneader, a Banbury mixer, etc. Among them, kneading using an extruder equipped with a degassing and decompression device is preferred from the perspective of productivity.
[0151] Alternatively, each component may be fed individually or several components may be fed together into an extruder continuously using a quantitative feeder or the like without mixing them in advance.
[0152] The kneading temperature may be determined according to the preferred processing temperature of the base resin, and may be, for example, 140 to 350°C, preferably 180 to 300°C.
[0153] [Base resin composition pellets]
[0154] The base resin composition pellets of the present embodiment include (a) polyarylether resin, (b) polystyrene resin and (c) metal salt. (a) polyarylether resin, (b) polystyrene resin and (c) metal salt may be the same as those included in the above-mentioned base resin composition, and the content thereof may be the same.
[0155] In addition, the base resin composition pellets of the present embodiment may optionally contain additives such as (d) flame retardants, (e) phosphorus antioxidants, (f) hindered phenol antioxidants, (g) hindered amine light stabilizers, and (h) other additives. As each additive, the same substances as those that can be contained in the above-mentioned base resin composition can be cited, and the content can also be the same.
[0156] The base resin composition pellets according to the present embodiment may be pellets obtained by pelletizing the base resin composition described above.
[0157] The base resin composition pellets of the present embodiment can be used for the production of a foamed molded article. The base resin composition pellets of the present embodiment can be foamed to produce foamed beads for obtaining a bead foamed molded article, or a foamed molded article can be directly produced.
[0158] By using the base resin composition pellets of the present embodiment, it is possible to obtain foamed beads having excellent moldability and foamability, and foamed molded products having excellent heat resistance, mechanical properties, and appearance.
[0159] The shape of the base resin composition pellets of the present embodiment is preferably a substantially circular cross-sectional shape when cut perpendicularly in the longitudinal direction, and may be a substantially columnar shape, a substantially spherical shape, etc., and a spherical shape is preferred.
[0160] It should be noted that, in this specification, substantially circular includes a perfect circle, an ellipse, or similar shapes with rounded corners. Substantially cylindrical includes not only a cylindrical shape with a constant cross section, but also a shape in which the cross section changes (a shape in which the cross section diameter decreases toward both ends in the length direction, etc.). Substantially spherical includes a perfect sphere, an elliptical sphere in the shape of a rugby ball, or similar shapes, etc.
[0161] In the present embodiment, the sphericity of the substrate resin composition pellets is 1.20 or less, preferably 1.15 or less. The lower limit of the sphericity of the substrate resin composition pellets is 1.00, preferably 1.05 or more. If the sphericity of the substrate resin composition pellets is within this range, the filling property during molding is more excellent, and it is easy to cool isotropically and uniformly during cooling after granulation, so it is not easy to generate voids.
[0162] In addition, the measurement of the sphericity of the base resin composition pellets can be carried out by the method described in the examples described later.
[0163] In the present embodiment, the average particle size of the substrate resin composition pellets is 0.50mm to 1.10mm, preferably 0.70mm to 1.00mm, and more preferably 0.80mm to 0.90mm. If the average particle size of the substrate resin composition pellets is within this range, it is easy to take into account both foamability and filling properties during molding. In addition, if the average particle size of the substrate resin composition pellets is less than 1.10mm, it is easy to cool evenly to the inside during cooling after granulation, so it also has the advantage of not being easy to produce pores. In addition, if the average particle size of the substrate resin composition pellets is less than 1.10mm, then in the impregnation process in the manufacture of the foamed particles described later, the foaming agent is easily impregnated into the pellets, and the generation of uneven foaming can be suppressed during foaming, and a foamed molded body with good appearance can be obtained.
[0164] In addition, the average particle diameter of the base resin composition pellets can be measured by the method described in the examples described later.
[0165] [Method for producing base resin composition pellets]
[0166] The method for producing the base resin composition pellets is not particularly limited, and examples thereof include a method of pelletizing the base resin composition by, for example, a thermal cutting method, an underwater cutting method, a strand cutting method, etc. Among these, the thermal cutting method and the underwater cutting method are preferred because pores are not easily generated near the pellet surface, and the underwater cutting method is preferred because it is easy to efficiently produce pellets having the above-mentioned characteristics that are nearly spherical.
[0167] When the underwater cutting method is used, the water pressure of the circulating water is preferably 1.0 to 2.0 bar. In this regard, it is believed that the following effects are achieved: by applying water pressure during cutting, the formation of cavitation in the water can be suppressed, cutting damage can be prevented, and the pellets can be made into a uniform shape; and by applying pressure to the molten resin coming out of the die head, the pellet shape can be made closer to a spherical shape.
[0168] In addition, the higher the temperature of the circulating water for underwater cutting, the more preferred it is, preferably 90° C. or higher, more preferably 95° C. or higher. By keeping the temperature of the circulating water within the above range, the cooling rate of the molten resin can be slowed down, the temperature difference between the surface and the inside of the resin can be reduced, and the generation of voids can be easily suppressed, or even if voids are generated, their size can be easily reduced.
[0169] It should be noted that in this specification, pressure is indicated by gauge pressure.
[0170] [Foaming particles]
[0171] The foamed particles of the present embodiment are foamed particles formed by foaming a base resin composition containing (a) a polyarylether resin, (b) a polystyrene resin, and (c) a metal salt. As the (a) polyarylether resin, (b) polystyrene resin, and (c) metal salt, the same substances as those contained in the above-mentioned base resin composition can be cited, and the content can also be the same.
[0172] In addition, the foamed beads of this embodiment may optionally contain additives such as (d) flame retardants, (e) phosphorus antioxidants, (f) hindered phenol antioxidants, (g) hindered amine light stabilizers, and (h) other additives. As each additive, the same additives as those that can be contained in the above-mentioned base resin composition can be cited, and the content can also be the same.
[0173] The foamed beads of the present embodiment may be formed by foaming the base resin composition or by foaming pellets of the base resin composition.
[0174] In the expanded beads of the present embodiment, the average cell diameter can be further reduced, and the variation in cell diameter can be controlled to be small, and the moldability and expandability are good, so that a bead expanded molded product excellent in heat resistance, mechanical properties, and appearance can be obtained.
[0175] The expansion ratio of the foamed particles of the present embodiment is preferably 3 to 50 cc / g, more preferably 5 to 15 cc / g, and still more preferably 6 to 12 cc / g. If the expansion ratio of the foamed particles is 50 cc / g or less, the independent bubble ratio is high, and there is a tendency to exhibit excellent moldability. If the expansion ratio of the foamed particles is 3 cc / g or more, there is a tendency to fully achieve the purpose of lightweighting the parts.
[0176] The closed cell ratio of the expanded beads of the present embodiment is preferably 80% or more, more preferably 90% or more, and further preferably 95% or more. When the closed cell ratio of the expanded beads is 80% or more, excellent moldability tends to be exhibited.
[0177] In the present embodiment, from the aspect of showing excellent heat resistance, the glass transition temperature Tg of the foamed particles is preferably 135°C or more, more preferably 145°C or more, further preferably 155°C or more, and most preferably 170°C or more. If the glass transition temperature Tg is 130°C or more, the heat resistance tends to be more excellent. In addition, the glass transition temperature Tg of the foamed particles is preferably 220°C or less, more preferably 200°C or less, and further preferably 190°C or less. If the glass transition temperature is 220°C or less, the temperature at which the bead foaming molded body can be molded will not be too high during the foaming of the bead foaming molded body, and there is a tendency to easily mold the bead foaming molded body.
[0178] The glass transition temperature Tg of the foamed beads can be adjusted by the same method as the glass transition temperature Tg of the above-mentioned base resin composition.
[0179] The glass transition temperature Tg of the foamed beads is the peak temperature of the loss tangent (tan δ) peak obtained by dynamic viscoelasticity measurement, similarly to the glass transition temperature Tg of the base resin composition, and can be measured by the method described in the examples below.
[0180] [Method for producing foamed particles]
[0181] The method for producing the foamed particles of the present embodiment is not particularly limited, and examples thereof include a method comprising the following steps: a granulation step for preparing pellets of a substrate resin composition; an impregnation step for impregnating the pellets of the substrate resin composition with a foaming agent; and a foaming step for foaming the pellets of the substrate resin composition to obtain foamed particles.
[0182] <Granulation process>
[0183] In the granulation step, the method for kneading the components of the base resin composition is not particularly limited, and for example, the method may be the same as that described in the above-mentioned [Method for Producing Base Resin Composition], and the kneading temperature may be the same.
[0184] In the granulation step, the method for pelletizing the base resin composition after extrusion is not particularly limited, and for example, it can be the same as the method described in the above-mentioned [Method for producing base resin composition pellets]. When using the underwater cutting method, the water pressure, temperature and other conditions of the circulating water can also be the same.
[0185] <Impermeation process>
[0186] In the impregnation step, the method for making the base resin composition contain a foaming agent is not particularly limited, and a commonly used method can be applied. As a method for making it contain a foaming agent, for example, there can be mentioned: a method using a suspension system such as water in an aqueous medium (suspension impregnation); a method using a thermal decomposition type foaming agent such as sodium bicarbonate (foaming agent decomposition method); a method of making the gas in an atmosphere above the critical pressure, making it in a liquid phase and contacting it with the base resin composition (liquid phase impregnation); a method of making the gas contact the base resin composition in a gas phase under a high pressure atmosphere below the critical pressure (gas phase impregnation); etc. Among them, the method of gas phase impregnation of the gas under a high pressure atmosphere below the critical pressure is particularly preferred.
[0187] Compared with the suspension infiltration implemented under high temperature conditions, in the method of gas phase infiltration, the solubility of gas in the resin is better, and it is easy to increase the content of the foaming agent. Therefore, it is easy to achieve a high foaming ratio, and the bubble size in the substrate resin composition is also easy to become more uniform. The foaming agent decomposition method can not only be implemented under high temperature conditions, but also the added thermal decomposition type foaming agent is not all converted into gas, so the gas generation amount is easy to be relatively reduced. Therefore, gas phase infiltration has the advantage of being easier to increase the content of the foaming agent. In addition, compared with liquid phase infiltration, in gas phase infiltration, equipment such as pressure-resistant devices and cooling devices are more likely to become compact, and it is easy to suppress equipment costs to a lower level.
[0188] The gas phase infiltration conditions are not particularly limited. As the atmospheric pressure, it is preferably 0.5 to 6.0 MPa, and more preferably 2.0 to 4.0 MPa. In addition, the atmospheric temperature is preferably 5 to 30°C, and more preferably 7 to 20°C. In addition, the infiltration time is preferably 2.0 to 6.0 hours, and more preferably 2.5 to 4.0 hours. If the atmospheric pressure, atmospheric temperature, and infiltration time are within the above ranges, it is easy to dissolve the gas in the substrate resin composition more effectively. In particular, if the atmospheric temperature is low, there is a situation where the infiltration amount increases but the infiltration rate slows down. If the atmospheric temperature is high, there is a tendency that the infiltration amount decreases but the infiltration rate becomes faster. In order to effectively dissolve the gas in the substrate resin composition according to its balance, it is preferred to set the above-mentioned atmospheric temperature.
[0189] The blowing agent is not particularly limited, and commonly used gases can be used. Examples thereof include inorganic gases such as air, carbon dioxide, nitrogen, oxygen, ammonia, hydrogen, argon, helium, and neon; fluorinated hydrocarbons such as trichlorofluoromethane (R11), dichlorodifluoromethane (R12), chlorodifluoromethane (R22), tetrachlorodifluoroethane (R112), dichlorofluoroethane (R141b), chlorodifluoroethane (R142b), difluoroethane (R152a), HFC-245fa, HFC-236ea, HFC-245ca, and HFC-225ca; aliphatic hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, and neopentane; Ethers such as ether, diethyl ether, methyl ethyl ether, isopropyl ether, n-butyl ether, diisopropyl ether, furan, furfural, 2-methylfuran, tetrahydrofuran, tetrahydropyran, etc.; ketones such as dimethyl ketone, methyl ethyl ketone, diethyl ketone, methyl n-propyl ketone, methyl n-butyl ketone, methyl isobutyl ketone, methyl n-amyl ketone, methyl n-hexyl ketone, ethyl n-propyl ketone, ethyl n-butyl ketone, etc.; alcohols such as methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, etc.; carboxylic acid esters such as methyl formate, ethyl formate, propyl formate, butyl formate, pentyl formate, methyl propionate, ethyl propionate, etc.; chlorinated hydrocarbons such as methyl chloride and ethyl chloride; etc.
[0190] These substances may be used alone or in combination of two or more.
[0191] From the aspect of flame retardancy, the foaming agent preferably does not have flammability and combustion-supporting properties. From the aspect of gas safety, inorganic gases are more preferred. In addition, inorganic gases are less soluble in resins than organic gases such as hydrocarbons. After the foaming process or the molding of the bead foaming molded body, the gas is easily extracted from the substrate resin composition, so the bead foaming molded body has the advantage of better dimensional stability over time. In addition, it also has the following advantages: it is not easy to cause plasticization of the resin due to residual gas; it is easy to show excellent heat resistance from an earlier stage after molding. Among inorganic gases, carbon dioxide is preferred from the aspects of solubility in resin and ease of handling.
[0192] The impregnation amount of the foaming agent is preferably 3 to 13 parts by mass, more preferably 3.5 to 10 parts by mass, based on 100 parts by mass of the resin contained in the base resin composition.
[0193] If the impregnation amount of the foaming agent is 3 parts by mass or more, a higher expansion ratio can be easily achieved, the variation of the bubble size in the base resin composition can be suppressed, and the variation of the expansion ratio between base resin compositions tends to be reduced. If it is 13 parts by mass or less, the bubble size does not become too small, the tendency of excessive foaming can be suppressed, and thus there is a tendency to easily maintain the independent bubble ratio.
[0194] <Foaming process>
[0195] There is no particular limitation on the foaming method of the foamed particles in the foaming step, and examples thereof include the following methods: a method of suddenly opening a high-pressure condition to a low-pressure atmosphere to expand the foaming agent (gas, etc.) dissolved in the base resin composition; a method of heating with pressurized steam, hot air, etc. to expand the foaming agent (gas, etc.) dissolved in the base resin composition; and the like.
[0196] Among them, the method of heating and foaming is particularly preferred because the size of the bubbles inside the base resin composition can be easily made uniform compared with the method of suddenly opening from a high pressure condition to a low pressure atmosphere.
[0197] The pressurized steam, which has the advantage of being easy to control the expansion ratio, especially easy to control the low expansion ratio products, is introduced from a plurality of steam holes, for example, in the lower part of the foaming furnace, and the resin is stirred by a stirring paddle, thereby enabling more uniform and effective foaming. The rotation speed of the stirring paddle is preferably 20 to 120 rpm, and more preferably 50 to 90 rpm. If the rotation speed is above 20 rpm, it is easy to contact the pressurized steam evenly, so it is easy to control the foaming, and there is a tendency that it is not easy to produce undesirable conditions such as adhesion. In addition, if the rotation speed is below 120 rpm, the foamed particles during foaming are not easily damaged by the stirring paddle, and there is a tendency that it is not easy to produce problems such as a decrease in the independent bubble rate or failure to obtain the desired foaming ratio.
[0198] In addition, a method of heating and foaming using high-temperature hot air is also preferred. This method is particularly effective when the glass transition temperature of the substrate resin composition (substrate resin composition pellets) is high. As a hot air foaming method, it can be any method of batch type or continuous type.
[0199] In the heating foaming method, the time from pressure release to reaching the maximum foaming temperature is preferably 20 seconds to 90 seconds, more preferably 25 seconds to 60 seconds, and even more preferably 25 seconds to 35 seconds.
[0200] Regarding the pressure relief, it can be 50% or less relative to the set pressure in the impregnation step. In addition, regarding the maximum foaming temperature, when using pressurized steam, it can be the temperature at which the maximum foaming pressure is reached, and when using hot air, it can be the maximum temperature of the hot air.
[0201] When the time from pressure relief to reaching the maximum foaming temperature is more than 20 seconds, the gas in the surface layer of the pellet diffuses, so that the foamed particles with reduced bubble diameter and reduced bubble diameter deviation can be produced while maintaining the thickness of the outer skin layer. In addition, when the time from pressure relief to reaching the maximum foaming temperature is less than 90 seconds, the gas does not diffuse excessively, and the foamed particles with reduced bubble diameter and reduced bubble diameter deviation can be obtained, which is preferred.
[0202] When the foaming particles are foamed to the desired expansion ratio, in the foaming process, the foaming can be performed to the desired expansion ratio by one stage, or by multiple stages such as secondary foaming and tertiary foaming. In the case of foaming by multiple stages, it is preferred that the pre-foamed particles (referring to the foamed particles that are not foamed in the final stage, etc.) are pressurized using inorganic gas before the foaming of each stage. The gas used in the pressurized treatment is not particularly limited, and from the aspect of flame retardancy and the safety of the gas, inorganic gas is preferably used. As examples of inorganic gases, air, carbon dioxide, nitrogen, oxygen, ammonia, hydrogen, argon, helium, neon, etc. can be cited, and from the aspect of ease of handling and economy, carbon dioxide and air are preferably used, but are not limited thereto. The method for pressurized treatment is also not particularly limited, and a method for filling pre-foamed particles in a pressurized tank and supplying inorganic gas to the tank for pressurization can be cited.
[0203] In the expanded particles, if the aliphatic hydrocarbon gas remains in the foam, the resin will be plasticized due to the remaining gas, the glass transition temperature will be reduced, and there is a tendency that excellent heat resistance cannot be shown. In addition, the gas is slowly discharged over time, and thus dimensional changes are easily produced in the obtained bead foaming molded body. Therefore, the residual concentration (content) of the remaining aliphatic hydrocarbon gas is preferably less than 1000 volume ppm.
[0204] In order to reduce the residual concentration of aliphatic hydrocarbon gases remaining in the foamed particles to less than 1000 volume ppm, for example, an inorganic gas can be used as a foaming agent, or the foamed particles can be placed under high temperature (for example, the temperature can be set arbitrarily between 40°C and 80°C) for a long time to release the residual gas in a "ripening process".
[0205] It should be noted that in this specification, the residual concentration of aliphatic hydrocarbon gas refers to the value obtained by dividing the volume of aliphatic hydrocarbon gas contained in the bead foaming molded product by the volume of the foam (volume ppm), and 1 volume ppm (hereinafter also referred to as "ppm") is equivalent to 0.0001 volume %.
[0206] Usually, the foaming process forming the interface of substrate resin composition and bubble is the physical change that is unfavorable for interfacial free energy, therefore has the extremely slow feature that the generation speed of bubble nucleus is compared with the growth rate of bubble, as a result, average bubble diameter increases easily, and the deviation of bubble diameter increases easily.In addition, if from the infiltration process pressure relief, then along with the passage of time, gas diffuses (discharges) from substrate resin composition pellet, therefore if the time lengthens from the pressure relief until foaming, then bubble nucleus reduces, and average bubble diameter increases easily.In addition, if from the infiltration process pressure relief, then gas diffuses from the surface layer of substrate resin composition pellet, thus at the center and the surface layer of pellet, the infiltration amount of gas produces difference (surface layer is less than the gas infiltration amount at the center), therefore the surface layer is less than the bubble nucleus at the center (bubble diameter increases), at the center and the surface layer, the deviation of bubble diameter increases easily.
[0207] As the characteristic of the substrate resin composition that bubble diameter is particularly easy to increase, it is high that the glass transition temperature of substrate resin composition can be cited.The higher the glass transition temperature of substrate resin composition is, the more high heat is needed when foaming, and it is easy to cause insufficient heating and uneven heating.Therefore, the deviation of average bubble diameter and bubble diameter increases, and the independent bubble rate reduces, so formability is easily reduced.
[0208] The glass transition temperature of the base resin composition has the following characteristics: the less the content of the (d) flame retardant in the base resin composition, the easier it is to increase the glass transition temperature, and the larger the mass ratio (a) / (b) of the (a) polyarylether resin to the (b) polystyrene resin in the base resin composition, the easier it is to increase the glass transition temperature.
[0209] In addition, the higher the glass transition temperature of the base resin composition, the higher the heating temperature during foaming. As a result, the thickness of the outer skin layer (outermost layer) of the base resin composition pellets tends to be thin, and the bubbles tend to burst when foaming at a high ratio.
[0210] When the base resin composition of the present embodiment is used, it can be heated relatively slowly to be foamed, so that foamed beads having a small cell diameter and reduced variation in cell diameter can be produced while maintaining the thickness of the outer skin layer.
[0211] In the foaming process of this embodiment, the metal salt (c) has the effect of generating multiple bubble nuclei simultaneously in the base resin composition with a very small amount of compounding. Therefore, the average bubble diameter of the foamed particles can be further reduced and the deviation of the bubble diameter can be minimized without compromising the foamability, moldability, heat resistance and mechanical properties.
[0212] If the average bubble diameter and the deviation of the bubble diameter increase, the independent bubble rate of the foamed particles is further reduced, resulting in reduced moldability. The independent bubble rate of the bead foaming molded body composed of such foamed particles is also reduced in the same manner, resulting in significantly reduced heat resistance, mechanical properties, and appearance, and is therefore not preferred.
[0213] [Bead foamed article]
[0214] The beads foam molded product of the present embodiment is composed of the above-mentioned foamed particles.
[0215] The beads foam molded product of the present embodiment is composed of the above-mentioned foamed particles having excellent moldability and foamability, and thus has excellent heat resistance, mechanical properties, and appearance.
[0216] The expansion ratio of the beads foamed molded article of the present embodiment is preferably 3 to 50 cm 3 / g, more preferably 5 to 15 cm 3 / g, more preferably 9 to 12 cm 3 / g. If the expansion ratio of the bead foaming molded body is 50cm 3 / g or less, there is a tendency to exhibit excellent heat resistance, mechanical properties and appearance. 3 / g or more, there is a tendency that the purpose of weight reduction of parts can be sufficiently achieved.
[0217] The closed cell ratio of the beads foam molded article of this embodiment is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. When the closed cell ratio of the beads foam molded article is 80% or more, there is a tendency to exhibit excellent heat resistance, mechanical properties, and appearance.
[0218] <1% dimensional change temperature Ts of beads foamed article>
[0219] The temperature (referred to as 1% dimensional change temperature or heat resistance temperature) Ts at which the dimensional change rate of the bead foam molded product of this embodiment reaches 1% after heating for 24 hours is preferably 110°C or more, more preferably 115°C or more, further preferably 140°C or more, and most preferably 155°C or more. If the 1% dimensional change temperature Ts is within the above range, there is a tendency to obtain a bead foam molded product with excellent heat resistance while maintaining good moldability. The upper limit of the 1% dimensional change temperature Ts is not particularly limited, and for example, it can be 220°C or less. It should be noted that Ts is usually lower than the glass transition temperature (Tg) of the base resin composition constituting the bead foam molded product.
[0220] In addition, the 1% dimensional change temperature Ts of the beads foam molded article can be measured by the method described in the examples described later.
[0221] In addition, in the bead foam molded article of the present embodiment, the difference (Tg - Ts) between the glass transition temperature (Tg) of the base resin composition constituting the bead foam molded article and the 1% dimensional change temperature (Ts) of the bead foam molded article is preferably 40°C or lower, more preferably 25°C or lower, and further preferably 20°C or lower. If Tg - Ts is 40°C or lower, the molding temperature is close to the 1% dimensional change temperature (Ts) of the bead foam molded article (the dimensional change start temperature increases), so there is a tendency to obtain a bead foam molded article with excellent heat resistance while maintaining moldability. In addition, Tg - Ts is preferably 10°C or higher, more preferably 15°C or higher. If Tg - Ts is 10°C or higher, molding can be performed at a temperature lower than the glass transition temperature (Tg), so there is a tendency to easily mold the bead foam molded article.
[0222] As a method for adjusting Ts of the bead foam molded article, for example, the following can be cited: adjusting the Tg of the base resin composition; removing the residual stress of the foam particles and the bead foam molded article; and so on. The value of Ts can be roughly designed according to the Tg of the base resin composition, but even when using a base resin composition with the same Tg, by reducing the residual stress remaining in the foam particles and the bead foam molded article, Ts can be further increased. In order to reduce the residual stress of the foam particles and the bead foam molded article, it is necessary to place them in an environment with a sufficiently high temperature for a sufficient time. For example, when obtaining foam particles by foaming the base resin composition, the heating time at a sufficiently high heating temperature can be extended; in the manufacture of the bead foam molded article, the heating temperature or time of the molding process can be increased; the bead foam molded article after the molding process can be heat-treated; and so on.
[0223] <Heating dimensional change rate at a temperature of <Tg - 30°C>>
[0224] In the bead foam molded article of the present embodiment, the heating dimensional change rate at a temperature of Tg - 30°C is preferably 1.0% or lower, more preferably 0.8% or lower, and further preferably 0.7% or lower. If the heating dimensional change rate at a temperature of Tg - 30°C is 1% or lower, there is a tendency to obtain a bead foam molded article with excellent heat resistance while maintaining good moldability. The lower limit of the heating dimensional change rate at a temperature of Tg - 30°C is not particularly limited and can be, for example, 0.1% or higher.
[0225] It should be noted that the measurement of the heating dimensional change rate at a temperature of Tg - 30°C of the bead foam molded article can be carried out by the method described in the following examples.
[0226] [Manufacturing method of bead foam molded article]
[0227] There is no particular limitation on the method of using the foamed particles to form a bead foamed molded body, and for example, the following method can be cited: the foamed particles are filled into a molding cavity of a molding mold, and the foamed particles are expanded by heating and thermally welded to each other, and then the resultant is solidified by cooling to perform molding (this process is also referred to as a "molding process"). The method of filling the foamed particles is not particularly limited, and a known method can be used.
[0228] Before the foamed particles are filled into the molding cavity of the molding die, the foamed particles are preferably subjected to a gas-based pressure treatment. By imparting a certain gas pressure to the bubbles of the foamed particles, the foamed particles constituting the obtained foamed molded body are firmly welded to each other, which can improve the rigidity and appearance of the molded body. There is no particular limitation on the gas used in the pressure treatment, and air and inorganic gases are preferred from the perspective of ease of handling and economy. There is no particular limitation on the method of pressure treatment, and the following methods can be cited: the foamed particles are filled into a pressurized container, and then the pressurized gas is introduced, and the pressure is increased to a maximum pressure of 0.1 to 20 MPa in 10 minutes to 96 hours, thereby supplying gas to the pressurized container.
[0229] The heating method for molding the foamed beads can include heating with a heat medium such as steam, heating with a heater such as an IR heater, heating with microwaves, etc. When heating with a heat medium, a general heat medium can be used, but steam is preferred from the perspective of effectively heating the resin.
[0230] The molding method of bead foam molding using water vapor (steam foam molding) generally includes: using a mold with water vapor holes, a process called one-side / opposite-side heating to replace the air between the mold and the foamed particles with steam; a process called double-side heating to introduce steam from both sides of the mold to fully heat the foamed particles and fuse the foamed particles together; a cooling process of blowing water to cool the heated product; etc. In particular, the temperature of the double-side heating process is most likely to rise, so the residual stress of the bead foam molding can be controlled by controlling the temperature and time of the double-side heating process.
[0231] If the heating temperature of expanded particles is high, then expanded particles are easily welded to each other, and the residual stress of bead foam molding is easily reduced, so there is a tendency to improve formability, thermotolerance, outward appearance. But if the heating temperature is too high, then the bead foam molding has a tendency to produce shrinkage, warpage, etc. In addition, if the heating time of expanded particles is long, then expanded particles are easily welded to each other, and the residual stress of bead foam molding is easily reduced, so there is a tendency to improve formability, thermotolerance, outward appearance. But if the heating time is too long, then the bead foam molding will produce shrinkage, warpage, etc., or the cycle deterioration and formability deterioration.
[0232] From the above aspects, the heating temperature of the foamed beads in the molding process is preferably higher than the temperature of Tg-30°C of the base resin composition, and may be higher than the temperature of Tg-20°C, may be higher than the temperature of Tg-10°C, may be higher than Tg, or may be higher than Tg. In addition, the heating temperature of the foamed beads in the molding process is preferably lower than the temperature of Tg+50°C of the base resin composition, and may be lower than the temperature of Tg+30°C, or may be lower than the temperature of Tg+20°C.
[0233] In addition, from the above aspects, the heating time of the foamed beads in the molding process is preferably 10 seconds or more, can be 20 seconds or more, can be 40 seconds or more, and can be greater than 40 seconds. In addition, the heating time of the foamed beads in the molding process is preferably 180 seconds or less, can be 120 seconds or less, and can be 90 seconds or less.
[0234] For example, the molding process may include heating at a high temperature higher than Tg, or heating at a temperature above Tg for a long time exceeding 40 seconds.
[0235] [Other foamed products]
[0236] Other foamed molded products of this embodiment are foamed molded products other than the bead foamed molded products composed of the above-mentioned foamed particles (foamed molded products formed by foaming without using foamed particles), which are obtained by adding a foaming agent to the base resin composition or base resin composition pellets to foam them.
[0237] The other foamed molded product of the present embodiment is produced using the above-mentioned base resin composition or base resin composition pellets having excellent moldability and foamability, and therefore has excellent heat resistance, mechanical properties, and appearance.
[0238] The expansion ratio of the other foamed molded article of the present embodiment is preferably 3 to 50 cm 3 / g, more preferably 5 to 15 cm 3 / g, more preferably 9 to 12 cm 3 / g. If the expansion ratio of other foamed molded bodies is 50cm3 / g or less, there is a tendency to exhibit excellent heat resistance, mechanical properties and appearance. 3 / g or more, there is a tendency that the purpose of weight reduction of parts can be sufficiently achieved.
[0239] The closed cell ratio of the other foamed molded product of this embodiment is preferably 80% or more, more preferably 90% or more, and further preferably 95% or more. If the closed cell ratio of the other foamed molded product is 80% or more, it tends to exhibit excellent heat resistance, mechanical properties and appearance.
[0240] <1% dimensional change temperature Ts of other foamed molded products>
[0241] The temperature (referred to as 1% dimensional change temperature or heat resistance temperature) Ts at which the dimensional change rate of other foaming molded products of this embodiment reaches 1% after heating for 24 hours is preferably above 110°C, preferably above 115°C, more preferably above 140°C, and most preferably above 155°C. If the 1% dimensional change temperature Ts is within the above range, there is a tendency to obtain other foaming molded products with excellent heat resistance while maintaining good moldability. The upper limit of the 1% dimensional change temperature Ts is not particularly limited, for example, it can be below 220°C. It should be noted that Ts is usually lower than the glass transition temperature (Tg) of the substrate resin composition constituting the foaming molded product.
[0242] In addition, the 1% dimensional change temperature Ts of other foamed molded products can be measured by the method described in the examples described later.
[0243] In addition, in the other foaming molded body of the present embodiment, the difference (Tg-Ts) between the glass transition temperature (Tg) of the base resin composition constituting the other foaming molded body and the 1% dimensional change temperature (Ts) of the other foaming molded body is preferably 40°C or less, more preferably 25°C or less, and further preferably 20°C or less. If Tg-Ts is 40°C or less, the temperature at which molding can be performed is close to the 1% dimensional change temperature (Ts) of the other foaming molded body (the temperature at which the dimensional change starts increases), so there is a tendency to obtain other foaming molded bodies with excellent heat resistance while maintaining moldability. In addition, Tg-Ts is preferably 10°C or more, more preferably 15°C or more. If Tg-Ts is 10°C or more, molding can be performed at a temperature lower than the glass transition temperature (Tg), so there is a tendency to facilitate molding of other foaming molded bodies.
[0244] As a method for adjusting Ts of other foamed molded articles, for example, the following can be cited: adjusting the Tg of the base resin composition; removing the residual stress of the foamed particles and other foamed molded articles; and so on. The value of Ts can be roughly designed according to the Tg of the base resin composition. However, even when using a base resin composition with the same Tg, by reducing the residual stress remaining in the foamed particles and other foamed molded articles, Ts can be further improved. In order to reduce the residual stress of the foamed particles and other foamed molded articles, it is necessary to place them in an environment with a sufficiently high temperature for a sufficient time. For example, the following can be cited: when obtaining foamed particles by foaming the base resin composition, extending the heating time at a sufficiently high heating temperature; in the manufacture of other foamed molded articles, increasing the heating temperature or extending the time of the molding process; heat-treating other foamed molded articles after the molding process; and so on.
[0245] <Rate of dimensional change upon heating at a temperature of Tg - 30°C>
[0246] In other foamed molded articles of the present embodiment, the rate of dimensional change upon heating at a temperature of Tg - 30°C is preferably 1.0% or less, more preferably 0.8% or less, and still more preferably 0.7% or less. If the rate of dimensional change upon heating at a temperature of Tg - 30°C is 1% or less, there is a tendency to obtain other foamed molded articles with excellent heat resistance while maintaining good moldability. The lower limit of the rate of dimensional change upon heating at a temperature of Tg - 30°C is not particularly limited and can be, for example, 0.1% or more.
[0247] It should be noted that the measurement of the rate of dimensional change upon heating at a temperature of Tg - 30°C of other foamed molded articles can be carried out by the method described in the following examples.
[0248] [Method for manufacturing other foamed molded articles]
[0249] Other foamed molded articles can be manufactured by adding a foaming agent to the base resin composition or base resin composition pellets to make them foam.
[0250] As the foaming agent, it can be the same as the foaming agent that can be used in the above [Method for manufacturing foamed particles], and the impregnation amount can also be the same.
[0251] The method for foaming and molding other foamed molded articles is not particularly limited. For example, the extrusion foaming method, injection foaming method, etc. can be cited.
[0252] The extrusion foaming method is as follows: using an extruder, the foaming agent is pressed into the molten base resin composition (or base resin composition pellets) for melt-kneading, and then the pressure is released at the outlet of the extruder to obtain a foamed body in the shape of a plate, sheet, or column with a certain cross-sectional shape.
[0253] The kneading temperature may be determined according to the preferred processing temperature of the base resin composition, and may be, for example, 140 to 350°C, preferably 180 to 300°C.
[0254] The injection foaming method is a method in which a base resin composition containing a foaming agent is injected and filled in a molding cavity of a molding die in a molten state or a semi-molten state, and then foamed in the mold to obtain a foamed molded product.
[0255] The injection molding conditions may be based on the preferred processing conditions of the base resin composition.
[0256] Example
[0257] The present invention is described in more detail below by way of examples, but the present invention is not limited to the following examples.
[0258] The measurement and evaluation methods used in Examples and Comparative Examples are described below.
[0259] <Glass transition temperature Tg of base resin composition>
[0260] The base resin composition was subjected to dynamic viscoelasticity measurement using a rheometer ("Physica MCR301" manufactured by Anton-Paar) under the following conditions, and the peak temperature (°C) of the loss tangent (tan δ) was determined as the glass transition temperature (Tg) of the base resin composition.
[0261] Measuring fixture: SRF10
[0262] Measuring mode: Vibration γ
[0263] Strain: swing angle γ = 0.015%
[0264] Frequency: 1Hz
[0265] Measuring temperature: 20℃~200℃
[0266] Heating rate: 2℃ / min
[0267] Normal force: -0.3N
[0268] Measuring points: 180
[0269] Time unit: s
[0270] Sample size: 10mm×40mm×thickness 1mm
[0271] <Average Particle Size and Sphericity of Base Resin Composition Pellets>
[0272] For 100 pellets of the base resin composition, the length in the longitudinal direction was measured with a vernier caliper, and the average value was obtained as the average length (L) [mm]. After that, it was divided into two parts at the center of the longitudinal direction by vertical cutting along the longitudinal direction, and the major diameter and minor diameter were measured at the obtained cross section with a vernier caliper, and the average major diameter (R1) [mm] and the average minor diameter (R2) [mm] were obtained by averaging them. The average particle size (R) [mm] was obtained from the average major diameter (R1) and the average minor diameter (R2) using the following formula.
[0273] R=(R1+R2) / 2
[0274] In addition, the ratio (L / R) of the average length (L) to the average particle size (R) was defined as the sphericity.
[0275] <Expansion ratio of foamed particles>
[0276] Measure the mass W of the foamed particles with a bulk volume of about 20 cc in a beaker. p (g) After that, the volume V cannot be measured by water p (cc), the volume V p Divide by mass W p , the obtained value V p / W p (cc / g) is taken as the expansion ratio.
[0277] <Closed Cell Ratio of Foamed Particles>
[0278] The true volume (Vx) of the expanded particles with a known expansion ratio (cc / g) was measured using an air comparison type densitometer manufactured by Beckman Co., Ltd. p ) was measured and the independent bubble rate S was calculated by the following formula p (%).
[0279] S p (%) = {(Vx p -W p / ρ p ) / (Va p -W p / ρ p )}×100
[0280] Vx p : True volume of foamed particles (cm 3 )
[0281] V p : Volume of expanded particles (expansion ratio × mass) (cc)
[0282] W p : Mass of foamed particles (g)
[0283] ρ p : Density of the base resin composition of the foamed particles (g / cm 3 )
[0284] <Appearance of Foam Molded Article>
[0285] A foamed molded body of 150 mm × 150 mm × 3 mm thickness was prepared using each foamed molded body preparation method under the condition of a crack rate of 10%. For Examples 2 to 4 and Comparative Example 2, a foamed molded body of 150 mm × 150 mm × 25 mm thickness was also prepared. The obtained foamed molded body was visually confirmed, and the appearance of the foamed molded body was evaluated according to the following judgment criteria.
[0286] A: No filling failure was observed on the surface and ends of the foamed molded article.
[0287] B: Poor filling was observed on the surface and / or end of the foamed molded article.
[0288] C: A plate-shaped foamed product cannot be obtained and the appearance cannot be determined
[0289] <Foaming ratio of foamed article>
[0290] Referring to the production methods of each foamed molded body, samples were produced with a 30 mm square and a thickness of 3 mm as the standard. For Examples 2 to 4 and Comparative Example 2, samples were also produced with a 30 mm square and a thickness of 25 mm as the standard. m (g) The volume of the sample V is measured. m (cm 3 ) divided by mass W m , the obtained value V m / W m As the expansion ratio (cm 3 / g).
[0291] <Closed Cell Ratio of Foam Molded Article>
[0292] The expansion ratio (cm 3 The true volume (Vx / g) of a known foamed molded article (15 mm square, 3 mm thick, 15 mm square, 25 mm thick in Examples 2 to 4 and Comparative Example 2) m ) was measured and the independent bubble rate S was calculated by the following formula m (%).
[0293] S m (%) = {(Vx m -W m / ρ m ) / (Va m-W m / ρ m )}×100
[0294] Vx m : True volume of the foamed molded body (cm 3 )
[0295] Va m : Volume of the foamed molded body (foaming ratio × mass) (cm 3 )
[0296] W m : Mass of the foamed molded body (g)
[0297] ρ m : Density of the base resin composition of the foamed molded body (g / cm 3 )
[0298] <1% dimensional change temperature Ts of the foamed molded body>
[0299] Using the production method of each foamed molded body, prepare test pieces of a foamed molded body with dimensions of 150 mm × 150 mm × thickness 3 mm. Dry these test pieces in a drying oven (Satake Safe Bend Dryer N50-S5) at 60 °C for 24 hours to remove the moisture contained in the test pieces. For these test pieces, referring to the dimensional stability test at high temperature (Method B) described in JIS K6767, draw 3 straight lines each with a length of 100 mm at intervals of 50 mm parallel to each other longitudinally and transversely in a grid pattern at the center of the test piece. Then place the test pieces in a drying oven (Satake Safe Bend Dryer N50-S5) and heat them at a specified temperature for 24 hours. For the test pieces before and after the heating test, measure the lengths of the 3 longitudinal and 3 transverse lines drawn respectively, and find their average values. Then calculate the dimensional change rate according to the following formula. Conduct the same test while changing the heating temperature, and take the temperature at which the dimensional change rate exceeds 1% as the 1% dimensional change temperature Ts (°C).
[0300] Dimensional change rate (%) = {(L2 - L1) / L1} × 100
[0301] (In the formula, L1 represents the average value of the line dimensions [mm] before the heating test, and L2 represents the average value of the line dimensions [mm] after the heating test.)
[0302] <Dimensional change rate at Tg - 30 °C>
[0303] A test piece of a foamed molded body of 150 mm × 150 mm × 3 mm thickness was prepared using each method for preparing a foamed molded body. The test piece was dried for 24 hours using a drying oven (Satake Safe Bend Dryer N50-S5) at 60°C to remove the moisture contained in the test piece. For the test piece, referring to the dimensional stability test at high temperature (B method) described in JIS K6767, three straight lines of 100 mm in length were recorded in a grid-like manner in the longitudinal and transverse directions at intervals of 50 mm in the central part of the test piece, and then placed in a drying oven (Satake Safe Bend Dryer N50-S5) and heated for 168 hours at "the glass transition temperature Tg-30°C of the base resin composition constituting the foamed molded body". For the test piece before and after the heating test, the lengths of the three longitudinal and transverse lines recorded were measured, and the average value was calculated, and then the dimensional change rate was calculated according to the following formula.
[0304] Dimension change rate (%) = {(L2-L1) / L1}×100
[0305] (In the formula, L1 represents the average value of the wire size [mm] before the heating test, and L2 represents the average value of the wire size [mm] after the heating test.)
[0306] <Compression Strength of Foam Molded Article>
[0307] A test piece of a foamed molded body of 150 mm × 150 mm × 25 mm thickness was prepared using the production methods of each foamed molded body. The test piece was cut using a band saw to produce a compression test piece of 30 mm × 30 mm × 25 mm thickness. It should be noted that the test piece was prepared in such a way that the two surfaces perpendicular to the thickness direction of the six surfaces of the compression test test piece were the surface surfaces, and the remaining four surfaces were the cutting surfaces. For the compression test test piece, with reference to ISO 844, a universal testing machine ("Autograph AG-X plus" manufactured by Shimadzu Corporation) was used to measure the compressive strength (MPa) at 5% compression under an environment of 23°C and 50 RH%.
[0308] The raw materials used in Examples and Comparative Examples are described below.
[0309] (a) Polyarylene ether resin-1: modified polyphenylene ether resin S201A (manufactured by Asahi Kasei Corporation), weight average molecular weight 53,000
[0310] (b) Polystyrene resin-1: General-purpose polystyrene resin GP685 (manufactured by PS Japan Co., Ltd.)
[0311] (c) Metal salt-1: zinc sulfide (ZnS) Sachtolith HD (manufactured by Sachtleben), average primary particle size 0.3 μm
[0312] (c) Metal salt-2: zinc oxide (ZnO) Yinling A (manufactured by Mitsui Mining & Smelting Co., Ltd.), average primary particle size 0.3 μm
[0313] (c) Metal salt-3: zinc sulfide (ZnS) with an average primary particle size of 0.6 μm
[0314] (c) Metal salt-4: titanium monoxide (TiO) PF-711 (manufactured by Ishihara Sangyo Co., Ltd.), average primary particle size: 0.25 μm
[0315] (d) Flame retardant-1: Rabitle FP-110 (manufactured by Fushimi Pharmaceutical Co., Ltd.)
[0316] (e) Phosphorus-based antioxidant-1: ADKSTAB PEP-36 (manufactured by ADEKA Corporation)
[0317] (f) Hindered phenol antioxidant-1: ADKSTAB AO-80 (manufactured by ADEKA Corporation)
[0318] (g) Hindered amine light stabilizer-1: ADKSTAB LA-57 (manufactured by ADEKA Corporation)
[0319] (h) Other additives-1: Mica A-11 (manufactured by Yamaguchi-Mica Co., Ltd.), average primary particle size 3 μm
[0320] (h) Other additives-2: Talc Micro Ace K-1 (manufactured by Nippon Talc Co., Ltd.), average primary particle size 8 μm
[0321] (h) Other additives-3: Calcined kaolin Glomax LX (manufactured by Hayashi Chemicals Co., Ltd.), average primary particle size 1.2 μm
[0322] Examples and comparative examples are described below.
[0323] (Examples 1 to 8)
[0324] (a) polyarylether resin, (b) polystyrene resin, and (c) metal salt were mixed in the ratio shown in Table 1, heated and melted by an extruder, and then extruded, and cut by an underwater pelletizer manufactured by Econ to obtain base resin composition pellets. When cutting in water, the circulating water temperature was set to 90°C and the water pressure of the circulating water was set to 1.0 bar. The average particle size and sphericity of the obtained base resin composition pellets are shown in Table 1.
[0325] According to the method described in Example 1 of Japanese Patent Gazette No. 4-372630, substrate resin composition pellets are placed in a pressure-resistant container, the gas in the pressure-resistant container is replaced with dry air, and then carbon dioxide (gas) as a foaming agent is injected to impregnate the substrate resin composition pellets with carbon dioxide under the conditions of pressure 3.0 MPa and temperature 10°C for 3 hours.
[0326] Next, the base resin composition pellets were taken out from the pressure vessel and conveyed, and the base resin composition pellets were foamed in a foaming furnace using the maximum pressurized water vapor pressure shown in Table 2 while rotating the stirring blade at 77 rpm to obtain foamed particles. The time from depressurization to reaching the maximum foaming temperature was 30 seconds.
[0327] Here, the content of hydrocarbon gas in the expanded beads was measured by gas chromatography immediately after the expansion, but it was below the detection limit (0.01% by mass).
[0328] Afterwards, the foamed particles were placed in a container, and pressurized air was introduced (it took 4 hours to increase the pressure to 0.4 MPa, and then maintained at 0.4 MPa for 16 hours), thereby subjecting the particles to a pressurized treatment. The particles were filled into an in-mold molding mold with steam holes (crack rate 10%), heated by steam, and the foamed particles were mutually expanded and welded, and then cooled and taken out from the molding mold to obtain a bead foam molding composed of the foamed particles. The measurement and evaluation results of the various physical properties are shown in Tables 1 and 4.
[0329] (Examples 9-10, 12-17)
[0330] (a) polyarylether resin, (b) polystyrene resin and (c) metal salt were mixed in the ratio shown in Table 1 to obtain base resin composition pellets in the same manner as in Example 1. Table 1 shows the average particle size and sphericity of the obtained base resin composition pellets.
[0331] According to the method described in Example 1 of Japanese Patent Gazette No. 4-372630, substrate resin composition pellets are placed in a pressure-resistant container, the gas in the pressure-resistant container is replaced with dry air, and then carbon dioxide (gas) as a foaming agent is injected to impregnate the substrate resin composition pellets with carbon dioxide under the conditions of pressure 3.0 MPa and temperature 10°C for 3 hours.
[0332] Next, the base resin composition pellets were taken out from the pressure vessel, transported, and placed in a mesh cage, where they were heated for 30 seconds with hot air at the maximum hot air temperature shown in Table 3 for foaming under stirring to obtain foamed particles. The time from pressure release to reaching the maximum foaming temperature was 35 seconds.
[0333] Afterwards, the foamed particles were placed in a container, and pressurized air was introduced (it took 4 hours to increase the pressure to 0.4 MPa, and then maintained at 0.4 MPa for 16 hours), thereby subjecting the particles to a pressurized treatment. The particles were filled into an in-mold molding mold with steam holes (crack rate 10%), heated by steam, and the foamed particles were mutually expanded and welded, and then cooled and taken out from the molding mold to obtain a bead foam molding composed of the foamed particles. The measurement and evaluation results of various physical properties are shown in Table 1.
[0334] (Example 11)
[0335] Expanded beads and beads expanded molded products were obtained in the same manner as in Example 1 except that (a) polyarylether resin, (b) polystyrene resin, (c) metal salt and (d) flame retardant were further blended.
[0336] (Example 18)
[0337] In addition to (a) polyarylether resin, (b) polystyrene resin, (c) metal salt, (e) phosphorus antioxidant was further blended, and foamed beads and foamed articles were obtained in the same manner as in Example 9. The measurement and evaluation results of the physical properties are shown in Table 1.
[0338] (Example 19)
[0339] In addition to (a) polyarylether resin, (b) polystyrene resin, (c) metal salt, (f) hindered phenol antioxidant was further blended, and foamed beads and foamed articles were obtained in the same manner as in Example 9. The measurement and evaluation results of the physical properties are shown in Table 1.
[0340] (Example 20)
[0341] In addition to (a) polyarylether resin, (b) polystyrene resin, (c) metal salt, (g) hindered amine light stabilizer was further blended, and foamed beads and beads foamed molded products were obtained in the same manner as in Example 9. The measurement and evaluation results of various physical properties are shown in Table 1.
[0342] (Example 21)
[0343] (a) polyarylether resin, (b) polystyrene resin, and (c) metal salt were mixed in the ratio shown in Table 1, heated and melt-kneaded by an extruder, and then extruded, and the circulating water pressure was set to 0.2 bar. Expanded particles and beads were obtained in the same manner as in Example 9. The measurement and evaluation results of various physical properties are shown in Table 1.
[0344] (Comparative Examples 1 to 6)
[0345] Expanded beads and beads expanded molded products were obtained in the same manner as in Example 1 except that (c) the metal salt was not added and (a) the polyarylether resin and (b) the polystyrene resin were mixed in the ratio shown in Table 1. The measurement and evaluation results of the physical properties are shown in Tables 1 and 4.
[0346] (Comparative Example 7)
[0347] Except that the (c) metal salt was not compounded, expanded beads and beads expanded molded products were obtained in the same manner as in Example 9. Table 1 shows the measurement and evaluation results of various physical properties.
[0348] (Comparative Examples 8 to 10)
[0349] Expanded particles and beads expanded molded products were obtained in the same manner as in Example 9 except that (a) polyarylether resin, (b) polystyrene resin and (h) additives instead of (c) metal salt were mixed in the ratios shown in Table 1. Table 1 shows the measurement and evaluation results of various physical properties.
[0350]
[0351]
[0352] [Table 2]
[0353]
[0354] [Table 3]
[0355]
[0356] [Table 4]
[0357]
[0358] Industrial Applicability
[0359] The foamed beads of the present invention have excellent moldability, and the bead foamed molded body composed of the foamed beads has excellent heat resistance, mechanical strength, and appearance, and can be suitably used for automobile peripheral parts, electronic equipment peripheral parts, etc. In addition, according to the foaming base resin composition and base resin composition pellets of the present invention, foamed beads with good moldability and foamed molded bodies with excellent heat resistance, mechanical strength, and appearance can be obtained, so they can be suitably used in the manufacture of automobile peripheral parts, electronic equipment peripheral parts, etc.
Claims
1. A foamed particle, which is a foamed particle formed by foaming a base resin composition, characterized in that: The substrate resin composition comprises: (a) polyarylether resin, (b) polystyrene resin, and (c) a metal salt, 0.01 to 1 parts by mass of (c) a metal salt is contained based on 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin, The (c) metal salt is an oxide and / or sulfide of at least one metal selected from the group consisting of aluminum, magnesium, tin, zinc, titanium, chromium, manganese, nickel, cobalt and iron.
2. The foamed particles according to claim 1, wherein The average particle size of the (c) metal salt is 0.5 μm or less.
3. The foamed particles according to claim 1 or 2, wherein The (c) metal salt is an oxide and / or sulfide of zinc and / or titanium.
4. The foamed particles according to claim 3, wherein The (c) metal salt is a sulfide of zinc and / or titanium.
5. The foamed particles according to claim 3, wherein The (c) metal salt is zinc oxide and / or zinc sulfide.
6. The foamed particles according to claim 3, wherein The (c) metal salt is zinc sulfide.
7. The foamed particles according to claim 1 or 2, wherein: The base resin composition contains 0 to 0.1 parts by mass of (d) a flame retardant based on 100 parts by mass of the total mass of (a) the polyarylether-based resin and (b) the polystyrene-based resin.
8. The foamed particles according to claim 1 or 2, wherein The glass transition temperature of the substrate resin composition is 145°C to 200°C.
9. The foamed particles according to claim 1 or 2, wherein: The mass ratio (a) / (b) of the (a) polyarylether-based resin to the (b) polystyrene-based resin is 1.50 or more.
10. The foamed particles according to claim 1 or 2, wherein The base resin composition contains 0 to 0.05 parts by mass of (e) a phosphorus-based antioxidant based on 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin.
11. The foamed particles according to claim 1 or 2, wherein The base resin composition contains 0 to 0.05 parts by mass of (f) a hindered phenol antioxidant based on 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin.
12. The foamed particles according to claim 1 or 2, wherein The base resin composition contains 0 to 0.05 parts by mass of (g) a hindered amine light stabilizer based on 100 parts by mass of the total mass of the (a) polyarylether resin and the (b) polystyrene resin.
13. A bead foamed molded product, comprising the foamed beads according to claim 1 or 2.
14. The beads foamed molded article according to claim 13, wherein The closed cell ratio of the bead-formed foam is 90% or more.
15. A foaming substrate resin composition comprising: (a) polyarylether resin, (b) polystyrene resin, and (c) a metal salt, It is characterized in that 0.01 to 1 parts by mass of (c) a metal salt is contained based on 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin, The (c) metal salt is an oxide and / or sulfide of at least one metal selected from the group consisting of aluminum, magnesium, tin, zinc, titanium, chromium, manganese, nickel, cobalt and iron.
16. A substrate resin composition pellet comprising: (a) polyarylether resin, (b) polystyrene resin, and (c) a metal salt, It is characterized in that 0.01 to 1 parts by mass of (c) a metal salt is contained based on 100 parts by mass of the total mass of the (a) polyarylether-based resin and the (b) polystyrene-based resin, The (c) metal salt is an oxide and / or sulfide of at least one metal selected from the group consisting of aluminum, magnesium, tin, zinc, titanium, chromium, manganese, nickel, cobalt and iron, The sphericity of the base resin composition pellets is 1.00 to 1.20, The average particle size of the base resin composition pellets is 0.50 mm to 1.10 mm.
Citation Information
Patent Citations
JP1975051197A
JP1977017880B2
Production of modified thermoplastic resin
JP1984059724A
Modified polyphenylene ether resin improved in processability and oxidation stability
JP1988108059A
Production of polyphenylene ether resin having excellent color tone
JP1988152628A